Three new cryptic species of the lamprey genus Lampetra Bonnaterre, 1788 (Petromyzontiformes: Petromyzontidae) from the Iberian Peninsula. - Mateus, Catarina (2013)
The Iberian Peninsula is a repository for biodiversity, presenting high levels of endemism in both plants and animals. In this peninsular region, brook lampreys confined to small, isolated river basins evolved in allopatry giving rise to evolutionary lineages, as revealed by mitochondrial DNA markers. For a better understanding of the taxonomic status and relationships of Iberian populations of the genus Lampetra, we combined previous data from genetics and morphological analysis (assessed here), and describe three new species of the lamprey genus Lampetra Bonnaterre, 1788 in Portugal. In this region L. planeri actually represent a complex of cryptic species, each having smaller geographic ranges than L. planeri, and consequently, greater vulnerability to extinction. The description of Lampetra alavariensis sp. nov. is based on 36 specimens collected on Ribeira de Mangas, a tributary of river Esmoriz, in Northern Portugal. Lampetra auremensis sp. nov. is described on the basis of 31 specimens collected on Ribeira do Olival, a small tributary of river Nabão (Tagus basin). Finally, Lampetra lusitanica sp. nov. is described based on 38 specimens from Ribeira da Marateca, Sado river basin, the southernmost distribution of the genus Lampetra. The recognition of these new species will contribute to the conservation of these already imperilled taxa and will help prevent the extinction of three important evolutionary lineages.